Penerapan Konsep Arsitektur Tropis pada Perancangan Kampung Vertikal di Kawasan Kampung Aur Kota Medan - Fitri, Rahmadhani; Wildan, Ahmad (Jurnal Teknik dan Teknologi Indonesia, 2026)
Medan City is one of the cities in Indonesia that cannot be separated from the problem of population growth. The problem of increasing population growth causes the need for residential areas to expand. Based on this, the arrangement of residential areas with limited land is starting to be directed towards vertical housing by utilizing limited land, maximizing open space, and providing public facilities. This design method uses field observations, literature studies, interviews and documentation. Data collection techniques were carried out by compiling site data, building data, analysis and vertical village design concepts in accordance with the tropical architecture approach. Therefore, Vertical Village Design with a Tropical Architecture approach aims to produce residential areas that are livable, which emphasizes site analysis, environmentally friendly and energy efficient to create termal security in buildings.